2012
DOI: 10.1038/onc.2012.131
|View full text |Cite
|
Sign up to set email alerts
|

The miR-99 family regulates the DNA damage response through its target SNF2H

Abstract: Chromatin remodeling factors are becoming known as crucial facilitators of recruitment of repair proteins to sites of DNA damage. Multiple chromatin remodeling protein complexes are now known to be required for efficient double strand break repair. In a screen for microRNAs that modulate the DNA damage response, we discovered that expression of the miR-99 family of microRNAs correlates with radiation sensitivity. These microRNAs were also transiently induced following radiation. The microRNAs target the SWI/SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 46 publications
6
112
0
2
Order By: Relevance
“…Cells were used for experiments when they were around 60% to 70% confluent. Preferably, low passages (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were used. Irradiation assay Radiosensitivity assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were used for experiments when they were around 60% to 70% confluent. Preferably, low passages (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were used. Irradiation assay Radiosensitivity assay.…”
Section: Methodsmentioning
confidence: 99%
“…miRs playing a role in radioresistance have been described, although experiments were done in cell line pairs and not in a larger panel of cell lines (18)(19)(20).…”
Section: Radioresistance Of Head and Neck Cancermentioning
confidence: 99%
“…14,15 Additionally, accumulating evidences have unraveled that miRNAs exerted critical roles in modulating the DNA damage response. [16][17][18][19] Thus, it's reasonable to speculate that DNA damage responsive miRNAs may exert a crucial role in modulating cisplatin sensitivity and drug resistance. In this study, we sought to screen differentially expressed miRNAs against cisplatin treatment, and further investigate into the effects of the identified DNA damage responsive miRNAs on cisplatin sensitivity, elucidating a novel molecular mechanism in the development of cisplatin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs were selected to target more than one gene that is involved in different repair Genes involved in cell cycle checkpoint, nucleotide excision, base excision, double-strand break and mismatch repair pathways and the miRNAs targeting these genes are listed. These associations were either published previously [11,[47][48][49][50], or bioinformatics studies showed that these miRNAs target the mRNAs (http://www.targetscan.org/, http://www.microrna.org/microrna/home.do, http://mirdb.org/miRDB/) pathways to be able to have a general idea of the possible regulatory roles of miRNAs in DNA repair pathways. The expression of 20 miRNAs targeting these repair genes was analysed in 22 oocytes and 23 blastocysts, respectively.…”
Section: Resultsmentioning
confidence: 99%